Association between C reactive protein and coronary heart disease: mendelian randomisation analysis based on individual participant data - Wensley,F; Gao,P; Burgess,S; Kaptoge,S; Di,Angelantonio E; Shah,T; Engert,JC; Clarke,R; Davey-Smith,G; Nordestgaard,BG; Saleheen,D; Samani,NJ; et al. (British Medical Journal, 2011)
Objective To use genetic variants as unconfounded proxies of C reactive protein concentration to study its causal role in coronary heart disease.Design Mendelian randomisation meta-analysis of individual participant data from 47 epidemiological studies in 15 countries.Participants 194 418 participants, including 46 557 patients with prevalent or incident coronary heart disease. Information was available on four CRP gene tagging single nucleotide polymorphisms (rs3093077, rs1205, rs1130864, rs1800947), concentration of C reactive protein, and levels of other risk factors.Main outcome measures Risk ratios for coronary heart disease associated with genetically raised C reactive protein versus risk ratios with equivalent differences in C reactive protein concentration itself, adjusted for conventional risk factors and variability in risk factor levels within individuals.Results CRP variants were each associated with up to 30% per allele difference in concentration of C reactive protein (P<10−34) and were unrelated to other risk factors. Risk ratios for coronary heart disease per additional copy of an allele associated with raised C reactive protein were 0.93 (95% confidence interval 0.87 to 1.00) for rs3093077; 1.00 (0.98 to 1.02) for rs1205; 0.98 (0.96 to 1.00) for rs1130864; and 0.99 (0.94 to 1.03) for rs1800947. In a combined analysis, the risk ratio for coronary heart disease was 1.00 (0.90 to 1.13) per 1 SD higher genetically raised natural log (ln) concentration of C reactive protein. The genetic findings were discordant with the risk ratio observed for coronary heart disease of 1.33 (1.23 to 1.43) per 1 SD higher circulating ln concentration of C reactive protein in prospective studies (P=0.001 for difference).Conclusion Human genetic data indicate that C reactive protein concentration itself is unlikely to be even a modest causal factor in coronary heart disease.